2007
DOI: 10.1186/1471-2458-7-121
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic effect of cigarette taxes on the consumption of cigarettes, alcohol and betel nuts

Abstract: Background: Consumption of cigarettes and alcoholic beverages creates serious health consequences for individuals and overwhelming financial burdens for governments around the world. In Asia, a third stimulant -betel nuts -increases this burden exponentially. For example, individuals who simultaneously smoke, chew betel nuts and drink alcohol are approximately 123 times more likely to develop oral, pharyngeal and laryngeal cancer than are those who do not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 29 publications
1
25
0
1
Order By: Relevance
“…However, in contrast to studies that examine the effects of overall tobacco price, few studies have extended cross-price elasticity analyses to examine the specific association of cigarette taxes and alcohol consumption. Extant studies using an adult sample from Taiwan and an adolescent sample from the U.S. provide initial evidence that the public health benefits of cigarette taxation may extend beyond smoking-related outcomes to impact alcohol consumption (Dee, 1999; Lee, 2007; Lee et al, 2010). The current study is the first to utilize data from a large, prospective, population-based sample of U.S. adults to study the association of increases in cigarette taxes with drinking outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in contrast to studies that examine the effects of overall tobacco price, few studies have extended cross-price elasticity analyses to examine the specific association of cigarette taxes and alcohol consumption. Extant studies using an adult sample from Taiwan and an adolescent sample from the U.S. provide initial evidence that the public health benefits of cigarette taxation may extend beyond smoking-related outcomes to impact alcohol consumption (Dee, 1999; Lee, 2007; Lee et al, 2010). The current study is the first to utilize data from a large, prospective, population-based sample of U.S. adults to study the association of increases in cigarette taxes with drinking outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, surprisingly little attention has been allocated to the impact of cigarette taxation on drinking behaviors, and extant evidence indicates that increases in cigarette taxes are associated with reductions in drinking. In an adult sample, Lee and colleagues found that alcohol use consistently decreased as a function of increasing cigarette taxation in Taiwan (Lee, 2007; Lee et al, 2010). In an adolescent sample, Dee (1999) demonstrated a negative (but non-significant) relationship between higher cigarette taxes and reductions in alcohol consumption.…”
Section: Introductionmentioning
confidence: 99%
“…However, very little attention has been allocated to the effect of tobacco taxation on other associated health behaviors, such as alcohol use. A number of economic investigations have found that the cross-price elasticity between alcohol and tobacco is negative suggesting that the two behaviors function as complements (Lee 2007; Aristei & Pieroni 2010). In other words, increasing the tax on cigarettes will result in reductions in consumption of both alcohol and cigarettes.…”
Section: Part Ii: How Can Knowledge Of Alcohol-tobacco Interactions Bmentioning
confidence: 99%
“…Previous research has shown that consumption of coffee decreases as the unit price of cigarettes increases (i.e., caffeine is a complement to cigarettes (Bickel et al, 1992)). Likewise, increasing cigarette taxes decreases alcohol and marijuana consumption (Lee, 2007, Dee, 1999, Chaloupka et al, 1999, Pacula, 1998, Farrelly et al, 2001), suggesting that consumption of alcohol and marijuana may decrease following nicotine reduction.…”
Section: How Is a Nicotine Reduction Policy Related To The Consumpmentioning
confidence: 99%